Corruption crimes: trends in methodological and forensic support of investigations - Khlus, A.M. (Bulletin of the Karaganda University “Law Series”, 2023)
The state and prospects for the development of forensic science in the aspect of developing methods for investigating crimes are considered. Attention is focused on the current trend in the formation of methods, the content of which are general methodological recommendations intended for the investigation of several different types of crimes, combined into a single group based on similar characteristics. It seems that the presence of common features in different types of crimes determines the possibility of constructing integrated investigative techniques. Their construction involves the initial identification of general criminal law and forensic classification characteristics of crimes. The actualization of the interest of the scientific community in terms of the formation of theoretical knowledge and the construction of integrated investigative methods did not contribute to the development of unity in their name and structural content. There is an understanding of the need to conduct a classification analysis of a group of crimes for which an enlarged (general, basic, generic, etc. names) methodology for their investigation is being developed. To construct a similar methodology for investigating corruption crimes, it is proposed to be based on the characteristics of the subjects of acts (officials) and the sphere of official activity, which allows us to consider them as the basis for the forensic classification of corruption crimes. The significance of the enlarged (general, basic, group, etc.) methodology for investigating corruption crimes is seen in the fact that it will serve as the basis for developing new and improving existing private methods for investigating certain types of corruption crimes.